Pengaruh Pendapatan Asli Daerah dan Belanja Modal terhadap Kinerja Keuangan Pemda Kabupaten/Kota Provinsi Kalimantan Barat - Fahmi, Muhammad; Ningrum, Karin Yudha; Mariana, Dina; Rivaldi, Urai Achmad (Eksos, 2023)
The amount of local own-source revenue (PAD) in recent years has fluctuated, this is due to the local government's lack of attention in developing the potential to obtain regional sources of income other than regional taxes. The population and sample size in this study were 14 cities/regencies in West Kalimantan Province for more than 5 years, from 2018 to 2022. This study employs a descriptive quantitative approach with statistical analysis techniques, specifically SPSS version 25. The findings revealed that the independent variable represented by X1 has a significance of 0.000 < 0.05, implying that PAD has a significant and positive influence on the regional government's financial performance as the dependent variable. Capital expenditure is denoted as X2 and has a 0.005 < 0.05 significance, implying that it has a significant positive impact on the local government's financial performance as the dependent variable. Thus, the F test results in this study suggest that PAD and capital expenditure are independent variables that have a strong influence on the financial performance of local governments as the dependent variable, represented by (Y).